Difficulties Faced by Students on Arabic Writing Skill at Ma’had Umar bin Khattab for Women - Junaedi; Ainaini Ratna Noeri (Journal of Arabic Language Studies and Teaching, 2021)
The purpose of this study was to determine the implementation of writing skills learning, the difficulties faced by students, and to overcome the difficulties faced by final year students at Ma'had Umar Bin Al-khattab specifically for women Sidoarjo. This research is a type of field research, and based on the nature of the research, it is qualitative research. Data collection techniques used in this study were interviews, observation, and documentation. The data analysis used by the researcher is qualitative, the data analysis techniques used are condensation, data presentation, verification and conclusion. From this study, it was found that the implementation of learning writing skills, God willing, was by the proper learning steps. The difficulties faced by students in writing insya' include linguistic factors and non-linguistic factors. Efforts to overcome these difficulties are often done by giving writing exercises, inviting discussions and providing motivation.